Verb Tense Classification and Automatic Exercise Generation - Ferreira, Kledilson; Pereira Jr., Álvaro R. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2018)
This paper describes a system developed for verb tenses classification in the English language and automatic generation of verb-tenses-oriented exercises, based on texts for study chosen by the user. The classification rules were analyzed iteratively. This research brings a method for generation of exercises of transposition of verb tenses. By this method, it is possible to transpose each verb tense on a sentence to another verb tense. The verb tenses transposition method can also be applied in other contexts, making it easy to choose an action (verb) and applying it to verb tense.